INTERVIEW: “To live, as much as possible, according to precepts of philosophical thinking means to live by the law of the measure of things” - Maria SÂNGEORZAN (Studia Universitatis Babeș-Bolyai. Philosophia)
At his 90 years of age, Professor Ion Irimie may be rightly called a witness, based on what he’s lived through and what he’s written about difficult and interesting times. He grew up and was educated in the spirit of the Romanian interbellum school and then he chose an academic career, and succeeded in reaching the highest didactic rank: university professor. All his life he worked for only one employer: Babeș-Bolyai University in Cluj-Napoca. Since 1990 Professor Ion Irimie has been living in Germany with his family. Here he had the respite to develop his ideas - previously published in national journals - and to propose new ones. He wrote about reflection, information, causality, alienation, entropy, about Socrates and Jesus, and so on. He always did have a firm attitude, affirming and reaffirming his convictions frankly. This interview shows how a philosopher “cast into the world” in peaceful times that soon turned utterly unstable, sees life.